Мировоззрение Василия Шульгина в контексте событий 1917–1919 гг. в Киеве - Bortnowski, Antoni (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
Vasily Shulgin (1878-1976) was a Russian political activist of the beginning of the 20th century. He is also known as an active publicist and the author of several memoir books. Born in Kiev and considering himself a "little-Russian", Shulgin acted as a supporter of the unity of Ukraine and Russia and considered his native city as the cradle of "Russianness" as well as an integral part of the whole-Russian cultural circle. Shulgin's worldview, reflected in his memoirs devoted to the years 1917-1919, became the subject of this article.